Chronic and Recurrent Central Serous Chorioretinopathy Treated with Homoeopathy : An Evidence-based Case Report (Advancements in Homeopathic Research, 2022)
Central Serous Chorioretinopathy (CSCR) is characterized by development of macular oedema leading to blurred central vision and metamorphopsia. It’s usually unilateral and affecting young males. Exact aetiology is not fully understood but risk factors include emotional stress, hypertension, use of steroids, sleep disorders, tubercular diathesis, helicobacter pylori infection etc. Majority of cases resolve spontaneously within 3months but there are frequent chances of recurrence, while chronic form doesn’t resolve within 6 months. A 40-year-old male presented with fogginess in central vision in left eye for 7 months that was not responding to conventional treatment andhad its recurrence twice. Use of Homoeopathic Natrum sulphuricum 30C followed by Silicea 30C has achieved improvement in subjective symptoms and visual acuityin 5months and gradual resolution of sub retinal fluid within a year. There was no recurrence for last 2 years and it was assessed objectively by Optical coherence tomography test. This case demonstrates positive effect of homoeopathy in chronic and recurrent CSCR.
Keywords: Central serous chorioretinopathy; Homoeopathy; Natrium sulphuricum; Silicea